2017
DOI: 10.21106/ijtmrph.50
|View full text |Cite
|
Sign up to set email alerts
|

Working Conditions and Productivity among Nurses in Selected Hospitals in Southwest Nigeria

Abstract: Background: Occupational stress and burnout are both one of the factors that bedevil the healthcare sector in developing countries, particularly in Nigeria. The study explored the perceived impact of working condition on the productivity of nursing staffs in selected hospitals in south-west Nigeria.Methodology: Descriptive survey design, comprising of 200 respondents selected randomly. Data were collected using questionnaires and descriptive statistics were used to analyze the data generated. The reliability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…They further explained that they have lost passion for their profession because of work-related stress. A study conducted in Nigeria by Hanson, Onasoga and Babalola ( 2017 :28) confirmed that the workplace environment plays an integral part in the causation of stress because people spend most of their time in the work setting. It was indicated that professional nurses caring for MHCUs are prone to substance abuse because of the scope of their duty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They further explained that they have lost passion for their profession because of work-related stress. A study conducted in Nigeria by Hanson, Onasoga and Babalola ( 2017 :28) confirmed that the workplace environment plays an integral part in the causation of stress because people spend most of their time in the work setting. It was indicated that professional nurses caring for MHCUs are prone to substance abuse because of the scope of their duty.…”
Section: Discussionmentioning
confidence: 99%
“…It was indicated that professional nurses caring for MHCUs are prone to substance abuse because of the scope of their duty. It is also stated that some of the professional nurses suffer from headaches, sleep disturbances, chest pains and other related symptoms of stress (Hanson et al 2017 :34). A study conducted in the United States by Edward, Hercelinsky and Giandinoto ( 2017 :215) emphasised that there is a robust relationship between high levels of emotional exhaustion amongst professional nurses working in mental health institutions and high workload being experienced in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…More so, stress management is an intervention meant to lessen the effect of stressors at work [51]. However, these interventions may be personalized with the goal of enhancing a person's capacity to handle pressure [52]. Moreover, the main goal of stress management is to protect people's mental and physical health, quality of life, and daily productivity [33].…”
Section: Stress Managementmentioning
confidence: 99%
“…High levels of occupational stress predispose workers to illness and increase presenteeism, absenteeism, turnover, job dissatisfaction, adverse events and, consequently, impact on the care provided to the population. 13 For the reasons explained and the incipience of published studies that compare occupational stress in certified and noncertified primary care organizations, it is important to develop research that performs this analysis. 9,14 Such results may support actions to improve the working conditions and the quality of care provided to the community.…”
Section: Introductionmentioning
confidence: 99%